Implementation of School Work Plan (RKS) Based on Internal Quality Service Standards (SPMI) in Elementary Schools (Educational Management, 2022)
The purpose of this study was to find out the form of implementation of school work plans based on internal quality service standards in elementary schools. Methods of data collection is done through interviews, observations, and documentation. Observations are made to observe, find data from several facts regarding matters related to problems with the implementation of the school work plan being carried out. Interviews were conducted to obtain information regarding the implementation of the school plans used by elementary schools. Documentation of this research is in the form of school RKS documents and RKS implementation report documents, EDS documents and school quality report cards owned by schools as well as RKS implementation reports. Takalar South Sulawesi. The findings in this study show: 1). Description of the implementation of the internal quality audit mechanism in school work plans based on internal quality service standards at SDN Takalar Regency., 2). Supporting Factors for the internal quality audit mechanism in the School Work Plan based on internal quality service standards for primary schools, 3). Inhibiting Factors of the internal quality audit mechanism in the standard-based School Work Plan Internal quality services at UPT SDN No. 221 Labbumesang Presidential Instruction.